Two new species of Thalictrum L. in Iran. Issue 1 (8th January 2013) - Pakravan, Maneezheh; Assadi, Mostafa
Abstract: Two new species of the genus Thalictrum named Th. mazandaranicum Pakravan &Assadi and Th. tacabicum Pakravan & Assadi from Iran are described and illustrated, their differences to related species are discussed. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)